Stil in identiteta - Juvan, Marko (Jezik in slovstvo, 2003)
After the decline of the paradigm, based on the tratment of the text and author, research styles in literary studies became subject to serious criticism (textcentricity, aesthetic ideology, ogranicism, dualism). . Contextual approaches in literary studies and linguistics ascribe a new significance to the notion of 'style' as correlated with the humanistic conception of 'life-style': style is an index of the identity of a text and its subject in the multilingual aspect of culture.
Keywords: literarna veda; literary science; stil; tekstna lingvistika; kontekstualizem; identiteta; literarni diskurz